A Butyrylcholinesterase Camera Biosensor Tested for Carbofuran and Paraoxon Assay - Miroslav Pohanka; Jitka Zakova (International Journal of Analytical Chemistry)
Biosensors containing cholinesterase are analytical devices suitable for the assay of neurotoxic compounds. In the research on biosensors, a new platform has appeared some years ago. It is the digital photography and scoring of coloration (photogrammetry). In this paper, a colorimetric biosensor is constructed using 3D-printed multiwell pads treated with indoxylacetate as a chromogenic substrate and gold nanoparticles with the immobilized enzyme butyrylcholinesterase. A smartphone camera served for photogrammetry. The biosensor was tested for the assay of carbofuran and paraoxon ethyl as two types of covalently binding inhibitors: irreversible and pseudoirreversible. The biosensor exerted good sensitivity to the inhibitors and was able to detect carbofuran with a limit of detection for carbofuran 7.7 nmol/l and 17.6 nmol/l for paraoxon ethyl. A sample sized 25 μl was suitable for the assay lasting approximately 70 minutes. Up to 121 samples can be measured contemporary using one multiwell pad. The received data fully correlated with the standard spectrophotometry. The colorimetric biosensor exerts promising specifications and appears to be competitive to the other analytical procedures working on the principle of cholinesterase inhibition. Low-cost, simple, and portable design represent an advantage of the assay of the biosensor. Despite the overall simplicity, the biosensor can fully replace the standard spectroscopic methods.